Information Systems Design and Intelligent Applications Proceedings of Fifth International Conference INDIA 2018 Volume 2 - Satapathy, Suresh Chandra; Bhateja, Vikrant; Somanah, Radhakhrishna; Yang, Xin-She; Senkerik, Roman (Advances in Intelligent Systems and Computing, 2019)
The book gathers a collection of high-quality peer-reviewed research papers presented at the International Conference on Information System Design and Intelligent Applications (INDIA 2018), which was held at the Universite des Mascareignes, Mauritius from July 19 to 21, 2018. It covers a wide range of topics in computer science and information technology, from image processing, database applications and data mining, to grid and cloud computing, bioinformatics and many more. The intelligent tools discussed, e.g. swarm intelligence, artificial intelligence, evolutionary algorithms, and bio-inspired algorithms, are currently being applied to solve challenging problems in various domains.